Mechanical and Microstructural Properties of Bamboo Fiber-Reinforced Concrete Containing a Blend of Waste Marble Powder and Waste Glass Powder - Dejene Mengesha Gelanew; Belachew Asteray Demiss (Advances in Civil Engineering)
Using blended supplementary cementitious materials in the production of concrete has a contribution to make in reducing cement consumption, as well as having a negative environmental impact. The main objective of this study was to investigate the mechanical and microstructural properties of bamboo fiber-reinforced concrete containing a blend of waste marble powder (WMP) and waste glass powder (WGP) as a partial replacement for cement. To achieve these objectives, the physical and chemical properties of concrete ingredients were studied. The design mix was done as per the American Concrete Institute (ACI) mixing procedure by using 5%, 10%, 15%, and 20% blended WMP and WGP as a replacement for cement and 0.75% bamboo fiber as an addition. The mechanical tests were conducted after samples were cured for 7 and 28 days in water. The microstructural properties of the hardened concrete from three different mixes were also determined for the 28-day cured specimens. The study result indicated improvement in compressive strength, shear stress, and bond stress at M2 (10%), whereas maximum splitting tensile strength was achieved at M1 (5%). Moreover, scanning electron microscopy (SEM) showed a denser microstructure, whereas X-ray diffraction (XRD) illustrated portlandite, calcium aluminum silicate, quartz, and calcium silicate hydrate as common phases of the concrete structure. Eventually, the experimental finding implied that using a 10% blend of WMP and WGP as a partial replacement for cement and 0.75% bamboo fiber improves fresh and hardened concrete properties.